Neutrophil-derived Activin-A moderates their pro-NETotic activity and attenuates collateral tissue damage caused by Influenza A virus infection - Divolis, Georgios; Synolaki, Evgenia; Doulou, Athanasia; Gavriil, Ariana; Giannouli, Christina C.; Apostolidou, Anastasia; Foster, Martyn L.; Matzuk, Martin M.; Skendros, Panagiotis; Galani, Ioanna-Evdokia; Sideras, Paschalis (Frontiers in Immunology, 2024)
Background Pre-neutrophils, while developing in the bone marrow, transcribe the Inhba gene and synthesize Activin-A protein, which they store and release at the earliest stage of their activation in the periphery. However, the role of neutrophil-derived Activin-A is not completely understood. Methods To address this issue, we developed a neutrophil-specific Activin-A-deficient animal model (S100a8-Cre/Inhbafl/fl mice) and analyzed the immune response to Influenza A virus (IAV) infection. More specifically, evaluation of body weight and lung mechanics, molecular and cellular analyses of bronchoalveolar lavage fluids, flow cytometry and cell sorting of lung cells, as well as histopathological analysis of lung tissues, were performed in PBS-treated and IAV-infected transgenic animals. Results We found that neutrophil-specific Activin-A deficiency led to exacerbated pulmonary inflammation and widespread hemorrhagic histopathology in the lungs of IAV-infected animals that was associated with an exuberant production of neutrophil extracellular traps (NETs). Moreover, deletion of the Activin-A receptor ALK4/ACVR1B in neutrophils exacerbated IAV-induced pathology as well, suggesting that neutrophils themselves are potential targets of Activin-A-mediated signaling. The pro-NETotic tendency of Activin-A-deficient neutrophils was further verified in the context of thioglycollate-induced peritonitis, a model characterized by robust peritoneal neutrophilia. Of importance, transcriptome analysis of Activin-A-deficient neutrophils revealed alterations consistent with a predisposition for NET release. Conclusion Collectively, our data demonstrate that Activin-A, secreted by neutrophils upon their activation in the periphery, acts as a feedback mechanism to moderate their pro-NETotic tendency and limit the collateral tissue damage caused by neutrophil excess activation during the inflammatory response.